Assessing Nitrate Leaching in Crop Production through the Application of Crop Simulation Models with Experimental Data from Florida: SL514/SS727, 9/2024 - Sharma, Lakesh; Gupta, Rishabh; Zotarelli, Lincoln; Hoogenboom, Gerrit (EDIS, 2024)
Lysimeters are often used in research concerning nutrient leachate all over the globe. However, due to factors such as Florida's high water table (a condition when the water level stays relatively close to the soil surface) in some production areas, the assessment and collection of leachate are not feasible. Another obstacle to the use of lysimeters in field research is the fact that several types of irrigation methods are used in Florida (e.g., subirrigation with seepage or drain-tile, overhead, microsprinkler, and drip irrigation) requiring different strategies for leachate assessment. This publication focuses on the use of crop models as alternatives to estimate nitrate leaching from cropping systems at a field scale. This publication's target audience is growers, extension agents, crop consultants, representatives of the fertilizer industry, state and local agencies, students, instructors, researchers, and interested Florida citizens.